جرائم بورصة القيم المنقولة في التشريع الجزائري: أشكالها والعقوبات المقررة لها - شرف الدين, وردة (Revue jurisprudence, 2018)
جرائم بورصة القيم المنقولة في التشريع الجزائري: أشكالها والعقوبات المقررة لها